ALT-803 in the treatment of non-muscle-invasive bladder cancer: Preclinical and clinical evidence and translational potential - Chen, Wujun; Liu, Ning; Yuan, Yang; Zhu, Meng; Hu, Xiaokun; Hu, Wenchao; Wang, Shuai; Wang, Chao; Huang, Binghuan; Xing, Dongming (Frontiers in Immunology, 2022)
Bladder cancer (BCa) is one of the most common malignant tumors that cause death. Approximately 75%–85% of BCa develop non-muscle-invasive bladder cancer (NMIBC). BCG is the gold standard for avoiding cystectomy in the treatment of NMIBC. Unfortunately, up to 30% of patients do not respond to BCG treatment, and up to 70% of BCG responders relapse. FDA approved valrubicin (1998) and pembrolizumab (2020) for the treatment of BCG-unresponsive (BCGu) NMBIC. However, the complete remission (CR) rate for valrubicin and pembrolizumab was only 16% and 40.6%, respectively. ALT-803 (N-803) is an IL-15 superagonist and reduces tumor burden by promoting the proliferation and activation of NK cells and CD8+ T cells. FDA received (May 23, 2022) and accepted to review (July 28, 2022) the marketing submission of ALT-803 plus BCG for the treatment of BCGu NMIBC. However, FDA previously rejected the application for oportuzumab monatox (OM) due to lack the data comparing pembrolizumab on August 20, 2021. Interestingly, the clinical efficacy and safety of ALT-803 were higher than that of pembrolizumab and OM, suggesting that ALT-803 may be approved by FDA. This review aims to provide knowledge on the preclinical and clinical evidence of ALT-803 in the treatment of NMIBC to discuss its translational potential.